2015
DOI: 10.1007/s10529-015-1952-8
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional hierarchical scaffold fabricated by a combined rapid prototyping technique and electrospinning process to expand hematopoietic stem/progenitor cells

Abstract: Three-dimensional hierarchical scaffolds were coated with ECM protein to simulate a biomimetic environment or niche, and had a significant effect on the expansion potential of HSPCs without changing their phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Previous studies have confirmed that 3D scaffolds could support the better maintenance of HSCs. However, if use MSCs or ECM protein as feeder layer, their consequences could be improved, because of cellcell interaction between CD34+ cells and feeder cells or ECM [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have confirmed that 3D scaffolds could support the better maintenance of HSCs. However, if use MSCs or ECM protein as feeder layer, their consequences could be improved, because of cellcell interaction between CD34+ cells and feeder cells or ECM [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, we have shown that PCL nanofiber scaffold coated with fibronectin had a higher number of CD34+ cells and TNCs number than traditional culture medium [15]. In 2016, Kang, et al revealed that the culture of CB derived CD34+ in PCL coated with fibronectin and collagen had a greater number of TNC and CD34+ cells compared to 2D culture system [16].…”
Section: Enhanced Colony Formation Of the Cells Expanded In The Pcl-cmentioning
confidence: 92%
“…In a recent study, Kang et al evaluated the expansion of hematopoietic stem cells seeded onto a three ECM protein‐coated polycaprolactone/hydroxyapatite (PCL/HA)‐composed hierarchical scaffold constructed by ESRP. After three days of cell culture, HSCs cultured in presence of fibronectin showed higher proliferation rates and CD45 + CD34+, CD34 + CD38‐ ratios than collagen‐treated HSCs or controls . Thus, it was demonstrated that ESRP‐fabricated three dimensional hierarchical scaffolds are effective tools for the expansion of HSCs without modifying their phenotype.…”
Section: Physical Approachmentioning
confidence: 98%
“…In another comparative study, fibronectin-coated surface proved to have higher expansion potential in HSC and a higher percentage of CD34 + and CD45 + cells compared with when collagen I coating was used. Probably this is because fibronectin provided a larger surface for cell attachment and stronger adhesion forces in HSC ( Kang et al, 2016 ). A supporting role of MSC with HSC has been proven in many cocultures on various materials.…”
Section: Hematopoietic Stem Cells and Hematopoiesismentioning
confidence: 99%